Application value of multi-disciplinary collaborative diagnosis and treatment combined with CBL teaching model in gynecological oncology practice teaching - Wen, Fengrong; Mo, Julan; Li, Renxiang (Frontiers in Medicine, 2025)
BackgroundTo explore the application value of multi-disciplinary collaborative diagnosis (MDT) and treatment combined with the case-based learning (CBL) teaching method based on real clinical cases in gynecological malignant tumor practice teaching.MethodsA total of 120 clinical students who were interning in the Department of Gynecology in our hospital from January 2022 to June 2023 were selected and divided into a research group (n = 60) and a control group (n = 60) according to the random number table method. The research group adopted a MDT combined with the CBL teaching model, while the control group followed a traditional teaching model. After the two-month internship, the teaching faculty completed a self-evaluation form, and the students jointly evaluated the teaching effect through an exit assessment, which included basic theory, clinical skills, and case assessment. Additionally, a questionnaire survey was conducted to evaluate the student’s recognition of the teaching model and collect their opinions and suggestions.ResultsThe research group showed significantly higher scores in basic theoretical knowledge, clinical skills, and case analysis assessments compared to the control group (p < 0.05). The questionnaire survey results indicated that the research group outperformed the control group in knowledge acquisition, learning initiative, learning interest, clinical analysis ability, clinical diagnosis, treatment thinking, teamwork ability, literature retrieval, and reading ability, and clinical language expression ability (p < 0.05). Students’ feedback suggested increasing doctor-patient communication time and improving the doctor-patient communication skills.ConclusionMDT combined with the CBL teaching model based on real clinical cases can effectively foster autonomous learning, enhance the application of basic theoretical knowledge, and improves the quality of clinical teaching in gynecology. This method is worthy of promotion in clinical teaching.